2000
DOI: 10.1016/s0042-6989(00)00005-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrical multisite stimulation of the isolated chicken retina

Abstract: Visual prostheses such as subretinal implants are intended for electrical multisite excitation of the retinal network. To investigate relevant issues like spatial resolution and operational range, we have developed an in vitro method using microelectrode arrays to stimulate isolated retinae. Ganglion cell activity in the chicken retina evoked by distally applied spatial voltage patterns consisted of fast bursts, transient inhibition and delayed discharges, and depended on the amount, location and spatial patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
192
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(214 citation statements)
references
References 37 publications
15
192
1
6
Order By: Relevance
“…Rd1 mice (C3H/HeJ strain) were used as the animal model of retinal degeneration. The retinal patches were prepared as previously described (Stett et al, 2000). The animals were anesthetized with intramuscular injections of Zoletin 50 (zolazepam hydroxide, 125 mg/5 ml) and Rumpun (xylazine hydroxide, 23.32 mg/ml) sufficient to extinguish the forefoot withdrawal reflex.…”
Section: Retinal Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rd1 mice (C3H/HeJ strain) were used as the animal model of retinal degeneration. The retinal patches were prepared as previously described (Stett et al, 2000). The animals were anesthetized with intramuscular injections of Zoletin 50 (zolazepam hydroxide, 125 mg/5 ml) and Rumpun (xylazine hydroxide, 23.32 mg/ml) sufficient to extinguish the forefoot withdrawal reflex.…”
Section: Retinal Tissue Preparationmentioning
confidence: 99%
“…Perception of simple visual patterns or phosphenes have been reported from clinical trials of human blind patients (Veraart et al, 1998;Humayun et al, 1999;Humayun et al, 2003;Rizzo et al, 2003;Hornig et al, 2005). Based on an in-vitro model of retinal implant that consists of retinal patches mounted on a planar multielectrode array (MEA), several studies on the properties of electrically-evoked firing of retinal ganglion cells (RGCs) have increased the basic knowledge required to determine effective methods of visual stimulation (Stett et al, 2000;Jensen and Rizzo, 2007;Ryu et al, 2009b). Recently, we showed that RGC response strength can be effectively controlled by amplitude modulation of stimulation pulse trains so that light intensity variation can be encoded within the RGC spike trains (Ryu et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…D'autres aspects essentiels de ces prothèses sont ceux de leur géométrie (Sommerhalder et al 2004) et de leur biocompatibilité. Des études sont actuellement en cours chez l'animal pour évaluer l'effet des stimulations électriques sur le réseau neuronal in vivo et in vitro (Stett et al 2000 ;Salzmann et al 2006 ;Kolomiets et al 2010).…”
Section: Prothèses Rétiniennesunclassified
“…All subsequent manipulations were done under dim red light to maintain the retina in a dark-adapted state. The method used by Stett et al (2000) was modified for retinal preparation. Briefly, the eyeball was enucleated and the retina was isolated.…”
Section: In Vitro Recording Of Retinal Activitymentioning
confidence: 99%